Neurocognitive Changes in Sickle Cell Disease: A Comprehensive Review. Issue 4 (October 2022) - Sahu, Tarun; Pande, Babita; Sinha, Meenakshi; Sinha, Ramanjan; Verma, Henu Kumar
Background: Sickle cell disease (SCD) is a type of hemoglobinopathy characterized by abnormal hemoglobin molecules, which includes numerous acute and chronic complications. Ischemic stroke, silent cerebral infarction, headache, and neurocognitive impairment are the most common neurological complications associated with SCD. Summary: Acute anemia because of SCD can cause cognitive impairments because of cerebral hypoxia. Cognitive abnormalities in SCD manifest in various aspects such as working memory, verbal learning, executive functions, and attention. These neurocognitive impairments have been associated with poor functional results, such as transitioning from juvenile to adult care, adherence to medications, and unemployment. Key message: In this review, we focus on neurocognitive aspects of SCD patients based on different imaging techniques, psychological batteries, associated neuromarkers, and interventions for managing of cognitive deficiencies..